Dynamic Analysis Of Two Link Robot Manipulator For Control Design Using PID Computed Torque Control. - Jolly Atit Shah; S S Rattan (Institute of Advanced Engineering and Science, 2016)
Due to their advantage of high speed, accuracy and repeatability, robot manipulators have become major component of manufacturing industries and even now a days they become part of routine life. Two link robot manipulator is a very basic classical and simple example of robot followed in understanding of basic fundamentals of robotic manipulator. The equation of motion for two link robot is a nonlinear differential equation. For higher degrees of freedom, as the closed form solutions are very difficult we have to use numerical solution. Here we focused mainly on control of robot manipulator to get the desired position using combination of two classical methods PID and computed torque control method after deriving the equation of motion. For the same simulation is represented using MATLAB and compared with computed torque control method.